How do stand composition and cervid densities influence the forest floor vegetation in a multi-cervid species context? - Leemans, Clémentine (2021)
The cover of forest floor vascular plants has been decreasing in Sweden over recent decades. Cervid rely heavily on this vegetation for food. With this study, I showed that habitat type highly influences the quality and quantity of the forest floor vegetation. In general, Scots pine forests (Pinus sylvestris) had a higher density of ericaceous shrubs (Vaccinium spp and Calluna spp; family Ericaceae) than Norway spruce forests (Picea abies), deciduous and mixed forests. Bilberry shrubs (Vaccinium myrtillus) found in Scots pine forests were taller. In accordance with previous studies done in Scots pine forests only, I observed across several different types of forests that bilberry shrubs were shorter in areas where fallow deer (Dama dama) were present at higher densities. But yearly shoots were longer in areas where moose (Alces alces) were present at higher densities. Norway spruce plantations had low abundance of ericaceous shrubs, grasses and forbs, deciduous forests also had low abundance of ericaceous shrubs but supported high abundance of grass and forbs. The decrease in forest floor cover that has been observed in Sweden is remediable with changes in the choices of forest type.